Plasma microRNAs characterising patients with immune thrombo cytopenic purpura - Zuo, Bin; Zhai, Juping; You, Lifang; Zhao, Yunxiao; Yang, Jianfeng; Weng, Zhen; Dai, Lan; Wu, Qingyu; Ruan, Changgeng; He, Yang (Thrombosis and Haemostasis, 2017)
Altered microRNA (miRNA) expression has been reported in patients with immune thrombocytopenic purpura (ITP). However, the detailed expression profiling of cell-free circulating miRNAs in ITP patients has not been fully investigated. In this study, we aimed to examine plasma miRNAs in ITP patients and evaluate their diagnostic values. Plasma samples from 74 ITP patients and 58 healthy controls were obtained and allocated into discovery, validation, and therapy-response sets. Initial screen with a miRNA microarray assay identified 23 miRNAs with different levels between ITP patients and healthy controls (>1.5-fold changes; p<0.01). Subsequent quantitative real-time PCR confirmed eight up-regulated miRNAs (miR-320c, miR-642b-3p, miR-1275, miR-3141, miR-4270, miR-4499, miR-4739 and miR-6126) and three down-regulated miRNAs (miR-144–3p, miR-1281 and miR-3162–3p) in ITP patients. The levels of these circulating miRNAs varied, depending on ITP subtypes, i.e. newly-diagnosed, persistent and chronic ITP, and between treatment responders and non-responders. In receiver operator characteristic analysis, 10 miRNAs had positive diagnostic values (p<0.05) when tested individually. The diagnostic value improved when the miRNAs were analysed as a panel or together with the analysis of anti-platelet autoantibodies. Plasma miR-3162–3p levels were also found to positively correlate with platelet counts in ITP patients (r=0.338, p=0.01). Our results indicate that plasma miRNA profiles are altered in ITP patients and that the differentially expressed miRNAs may be used as biomarkers to improve the diagnosis of ITP.
Keywords: Biomarker; immune thrombocytopenic purpura; microarray; microRNA; platelet autoantibody